1977
DOI: 10.1136/vr.101.6.107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oestrus on milk production in cows

Abstract: The rectal temperatures, pulse rates and milk yields of 44 Ayrshire and 38 Friesian cows were recorded during oestrus and compared with values obtained after oestrus had ceased. The fat, solids-non-fat (SNF) and protein percentages and the cell counts of milk samples were also compared. Forty of the cows were housed in cubicles and 42 were kept loose in yards. During oestrus rectal temperatures and pulse rates were significantly raised and milk yields were lowered. Milk had, on average, significantly higher fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

1979
1979
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…Data from cattle about the effect of estrus on SCC is equivocal. One study showed an association between natural estrus and an increase in SCC (King 1977). However, several other studies failed to find an association between estrus and SCC (Guidry et al 1975;Cowan and Larson 1979;Anderson et al 1983).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Data from cattle about the effect of estrus on SCC is equivocal. One study showed an association between natural estrus and an increase in SCC (King 1977). However, several other studies failed to find an association between estrus and SCC (Guidry et al 1975;Cowan and Larson 1979;Anderson et al 1983).…”
Section: Discussionmentioning
confidence: 91%
“…An increase in SCC has been reported to coincide with the beginning of the breeding season (Lerondelle et al 1992) and associated with induction of estrus (Aleandri et al 1994) in dairy goats. In dairy cows, one study reported an increase in SCC at estrus (King 1977), whereas several other studies have found no effect of either natural or induced estrus on SCC (Cowan and Larson 1979;Anderson et al 1983).…”
Section: Introductionmentioning
confidence: 95%
“…There were no reports on the effect of oestrus on the she-camel milk that we know about till the day of the study. However, several previous studies in dairy cattle and dairy goat provided evidence of a decline in milk volume associated with oestrous (King, 1977;Cowan et Larson, 1979;Mc Dougall et Voermans, 2002;Lopez et al, 2005). Erb et al (1952) reported that this decline was more apparent as stage of lactation increased.…”
Section: Milking Parametersmentioning
confidence: 97%
“…In dairy cattle, several studies reported a decrease in milk yield and an increase in SCC and fat content during oestrus (King, 1977;Horrell et al, 1986;Lopez et al, 2005). Whereas, other studies state that oestrus have no effect neither on SCC (Anderson et al, 1983) nor milk yield and composition (Cowan and Larson, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in SCC have been reported coincident with the beginning of breeding season (Lerondelle et al 1992) and associated with induction of estrus (Aleandri et al 1994) in dairy goats. In dairy cows, one study reported an increase in SCC at estrus (King 1977). Other studies have found no effect of either natural or induced estrus on SCC (Cowan and Larson 1979;Anderson et al 1983).…”
Section: Introductionmentioning
confidence: 94%